PO.1.10 Multicentre study in sle patients with and without renal involvement by label free proteomic analysis of 24h urine. (27th September 2022) - Rivera, N; Ruiz, E; Calvo, J; Aurrecoechea, E; Riancho, L; De Diego-Sola, A; Diaz, M; Galindez, E; Fernandez, O; Torre, I; Cuende, E; Blanco, J; et al.
Abstract : Background: Lupus nephropathy (LN) is an important cause of morbidity and mortality in patients with Systemic Lupus Erythematosus (SLE). Considering that renal biopsy is a specialized technique and not risk free, a proteomics study is proposed to determine biomarkers that may help us to differentiate patients diagnosed with SLE with and without renal involvement. Methods: Prospective and multicentric study of proteomics was conducted in 24-hour urine from SLE patients with and without renal involvement, by label free nLC MS/MS analysis. Results: 124 patients were recruited from 5 centers: 49 patients with SLE and renal involvement and 73 patients with SLE without renal involvement. There were no differences between groups according to race, gender and age ( Table 1 ). A total of 718 proteins (identified with at least two peptides with a FDR<1%) were quantified and further considered in the analysis. The Student's T-test analysis reflected the differential presence of 518 proteins (p<0.01) between patients with and without renal involvement, being 58 more abundant in the urine of the patients with renal damage, whereas 460 showed the opposite pattern. Two diagrams (diagram 1 & 2) by biological process and protein class, show the results. Conclusions: In this multicentric study, a different protein pattern in urine (over or under expression) is observed between patients with and without renal involvement. It is necessary to continue with the study of the results in the context of cell biology, to know the basis of the deregulation of the proteins found among these groups of patients. On the other hand more studies are needed to know if proteomics analysis of urine could serve as diagnostic/prognostic tool of lupus patients with and without renal involvement.